Mekanisme Suplementasi Magnesium Glycinate Sebagai Terapi Adjuvan pada Pasien Depresi - Asfarina Prihandini; Jodii Arlan Kurnia (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Depression is a mood disorder characterized by feelings of sadness, loss of interest, and energy deficit. Furthermore, depression can lead to cognitive and somatic disorders, even suicidal ideation. Pharmacological therapy using antidepressants such as Selective Serotonin Reuptake Inhibitors (SSRI) and Serotonin-Norepinephrine Reuptake Inhibitors (SNRI) has proven effective but has several side effects. In the last decade, attention has shifted to micronutrients such as magnesium glycinate as adjuvant therapy. This literature review analyzes the latest scientific evidence regarding the neurobiological mechanisms of magnesium glycinate in supporting the management of depression. Magnesium glycinate works through several mechanisms; N-Methyl-D-Aspartate (NMDA) receptor antagonism to prevent excitotoxicity; modulation of monoamine and Gamma-Aminobutyric Acid (GABA) neurotransmitters for mood stabilization; increasing Brain Derived Neurotrophic Factor (BDNF) to support neuroplasticity; modulation of the hypothalamic-pituitary-adrenal axis (HPA axis); reduction of proinflammatory cytokines. Magnesium glycinate has high bioavailability and good gastrointestinal tolerance, making it promising as an adjunctive depression therapy and opening up opportunities for further clinical research.